Hspa13 Deficiency Impaired Marginal Zone B Cells Regulatory Function and Contributed to Lupus Pathogenesis - Chen Xing; Haoran Cui; Ge Li; Xiaoling Liu; Kun Liu; Qing Wen; Xin Huang; Renxi Wang; Lun Song (Advanced Science)
Abstract Dysregulated IL‐10 producing regulatory B cells (Bregs) are associated with the progression of systemic lupus erythematosus. An immunomodulatory role of heat shock proteins (HSPs) is implicated in autoimmune diseases. However, the molecular basis underlying the role of Hspa13 in regulating Bregs function and lupus pathogenesis remains unclear. In this study, Bregs display higher Hspa13 expression than IL‐10− B cells. Induction of IL‐10 production is weakened in B cells with Hspa13 knockdown or knockout. Hspa13 binds to the IL‐10 promoter via the TATA or CAAT box and activates IL‐10 transcription in the nucleus. Furthermore, Hspa13 positive cells are enriched in marginal zone (MZ) B cells to regulate IL‐10 production. Stimulated B220+ B or MZ B cells from CD19creHspa13fl/fl mice for Breg induction show an impaired capacity to promote CD4+Foxp3+ regulatory T cells (Treg) differentiation. In lupus MRL/lpr mice, a decline in Treg differentiation is accompanied by decreased Hspa13 expression in both Bregs and MZ B cells. Moreover, adoptive transfusion of Bregs and MZ B cells from CD19creHspa13fl/fl mice fails to increase the frequency of Tregs, attenuate renal pathology, or decrease anti‐dsDNA antibody levels. These results explain the unique role of Hspa13 in determining MZ regulatory function and affecting lupus pathogenesis.